Climate-Smart Maps and Adaptation Plans (CS MAP) of the 13 provinces in Vietnam’s Mekong River Delta - CGIAR Research Program on Climate Change, Agriculture and Food Security; Department of Crop Production (2018)
Climate-Smart Maps and Adaptation Plans (CS MAP), a participatory approach developed by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Department of Crop Production of Vietnam's Ministry of Agriculture and Rural Development, engages experts from the national and local levels to: identify climate-related risks; determine potential affected areas and their risk levels using technical, infrastructure and topographic data, and local knowledge; assess and improve proposed adaptive measures; and develop integrated adaptation plans for rice production from regional to provincial levels. Maps of flooding and salinity intrusion risks were developed by integrating scientific evidence provided by researchers and experts with local knowledge of stakeholders on topography, infrastructure, hydrological management schemes, and land use plans. Based on the risk maps, adaptive rice production calendars for moderate intensity and duration (normal year) and extreme intensity and prolonged duration (severe year) were generated. Through a series of consultations with provincial and regional stakeholders, the cropping schedules were proposed, not only to address various climate-related risks, but also to ensure sharing of resources and harmonization of policies concerning water, labor, infrastructure, and information.